Potential effect of decreased levels of folic acid and vitamin B12 on herpes simplex virus keratitis reactivation - Savić, Borivoje Milan; Stanojlović, Svetlana; Stojković, Milenko; Mišić, Miroslav; Savić, Božidar; Draganić, Veselin (Vojnosanitetski pregled, 2021)
Background/Aim. Most cases of herpetic keratitis present a recurrent disease as a result of herpes simplex virus type 1 reactivation from latency in the nearest sensory ganglia. Therefore, understanding the mechanisms of latency and reactivation of the latent virus is an important link in comprehending the onset of the recurrent eye disease itself. Epigenetic regulation of virus reactivation, as a result of the presence of transcriptionally active Latency-Associated Transcript (LAT) region in the latent viral genome, has already been demonstrated in several studies. The activity of the LAT region is directed to the chromatin arrangement. Epigenetic modulation of DNA methylation is associated with folate and vitamin B12 intake or their serum concentrations. To our knowledge, there is no report on the potential role of vitamin B12 and folic acid in herpes simplex virus keratitis reactivation. The aim of this study was to analyze the potential role of folic acid and vitamin B12 in the control of ocular herpes simplex keratitis reactivation. Methods. The study included 50 patients older than 18 years of age with recurrent herpes simplex virus eye disease. Levels of vitamin B12 and folic acid were measured in the acute phase of the disease. All patients were followed up for at least one year and episodes of recurrent herpetic eye diseases were recorded. Results. The recurrence rate of herpetic keratitis was statisticall significantly lower in patients with a higher blood level of vitamin B12. In addition, the recurrence rate of herpetic keratitis was lower in patients with a higher blood level of folic acid. However, statistical significance was lower in comparison with that for vitamin B12. Conclusion. The decreased levels of vitamin B12 and folic acid might have a vital role in herpes simplex keratitis reactivation.
Keywords: herpesvirus 1, human; folic acid; keratitis; recurrence; risk factors; vitamin b 12